Aesthetic Performance Products as a Basis For Non Novelty of Industrial Design Based on The Public Domain Principle - Desy Rizki Ramadhani; Puteri Melati; Camellia Anand (Notaire, 2019)
Comparative products are very important and must be considered about it because, Industrial Design assesses the performance of products that can be proven from evidence that can be seen or assessed by clear eye such as photographic evidence, catalogs or other evidence that can be proved bye Industrial Design which has existed before. Industrial design is based on its external appearance which does not have an aesthetic impression and contradicts Article 1 point 1 of the Industrial Design Law and article 25 Paragraph 1 of the TRIPs agreement, which is form creation, solely for function or technical configuration. Aesthetically cannot be registered. In the absence of aesthetic elements, the product performance can be used as the basis for the absence of new industrial designs based on the principle of "Public Domain", considering the aesthetic elements are one of the requirements of an item that can be categorized as Industrial Design. In the other hand, the protection period has expired and became a "Public Domain" then it can be registered as an Industrial Design if it packed with an aesthetic elements. If an item does not have an aesthetic impression, it can be ascertained that the item is not an industrial design and can be possible not to have novelty and become public property. Aesthetic impressions do not contradict with the laws and regulations, but this is an important requirement so the design can be categorized as an industrial design. In ordinance No. 31 in 2000 concerning Industrial Design itself does not limit of the notion novelty and aesthetics so, the multiple interpretations are often occur.